Single-Metal-Anchored 1D Mesoporous Channels to Enable Accelerated Redox Kinetics for Lithium-Sulfur Batteries - Zhao, Dequn; Wang, Shun; Zhang, Yanan; Zhang, Xingxing; Hou, Xuehan; Wang, Hong; Liu, Xiangyu; Yin, Feiyang; Zhou, Wei; Huang, Wenhuan (Nano-Micro Letters, 2026)
Metal–organic frameworks (MOFs) have been demonstrated as promising separators for lithium-sulfur batteries (LSBs) owing to their highly tunable porous structures and intrinsic metal sites, which can guide uniform Li+ deposition, catalyze polysulfide conversion, and suppress polysulfide shuttling. However, conventional MOFs often have insufficient catalytic activity and Li+ transport control, and the role of their internal pore structure in regulating Li+ flux and polysulfide conversion remains unclear, limiting their effectiveness as high-performance separators. Herein, we report a series of azolate hybrid frameworks (M-AHF-DPDC, M = Fe, Co, Ni) featuring one-dimensional anionically charged channels that implement a dual-function regulation mechanism, simultaneously promoting uniform Li+ flux and catalyzing polysulfide conversion. Incorporation of Fe centers significantly enhances polysulfide redox kinetics, resulting in superior electrochemical performance, including a high initial capacity of 1400.7 mAh g−1 and stable cycling over 700 cycles at 1 C, along with uniform Li+ deposition, outperforming most reported MOF-based separators. Density functional theory calculations confirm that Fe sites strongly adsorb and catalytically convert diverse polysulfides, promoting rapid sulfur species transformation. This work demonstrates that the synergistic combination of polysulfide blocking and catalytic conversion enhances LSBs performance and offers a feasible strategy for high-energy–density rechargeable lithium-sulfur batteries. Highlights: 1 An innovative azolate hybrid framework featuring dual-functional one-dimensional lithiophilic channels was constructed and applied to designing M-AHF-DPDC (M = Fe, Co, Ni) separator. Its unique framework design, equipped with lithiophilic channels and dense Fe active sites, enables uniform Li+ transport and efficient catalytic activity. 2 The Fe-AHF-DPDC-modified separator significantly enhances the cycling stability and energy density of Li–S batteries while effectively suppressing the polysulfide shuttle effect. 3 Through in situ Raman spectroscopy and density functional theory calculations, the strong adsorption capability and catalytic conversion mechanism of Fe-AHF-DPDC toward lithium polysulfides were elucidated.